Pembuatan Logo sebagai Merek dari Kerajinan Pipiti untuk Souvenir dalam Mendukung Desa Wisata Kawungluwuk - Najwa Abdillah; Syafiqah Mahdiah Dai; Rinie Octaviany Hasan; Nining Nining (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
This activity strengthens pipiti handicrafts' identity as a signature souvenir of Kawungluwuk Tourism Village through branding development, including a brand name, logo, and philosophy based on local wisdom. The partners' challenge is that pipiti products lack a clear brand identity, resulting in limited appeal and competitiveness. The activity used Participatory Action Research (PAR), emphasizing active partner participation from problem identification to implementation. The stages included designing the brand name, logo, and philosophy; branding education; and handover of design results. The branding produced the name "PipitUng," a bamboo-based logo, and the philosophy "grown from nature, living within culture," reflecting local wisdom. Implementation included a logo application simulation on products and delivery of the logo in digital and printed formats. This activity contributes to strengthening pipiti's identity, enhancing its appeal as a souvenir, and opening opportunities for increased economic value and sustainable artisan businesses rooted in local wisdom.